Identification of inhibitors targeting ferredoxin-NADP+ reductase from the Xanthomonas citri subsp. citri phytopathogenic bacteria - Martínez-Júlvez, Marta (2017)
Fil: Fil: Martínez-Júlvez, Marta. Universidad de Zaragoza. Facultad de Ciencias e Institute of Biocomputation and Physics of Complex Systems (BIFI-IQFR and CBsC-CSIC Joint Units). Departamento de Bioquímica y Biología Molecular y Celular; España.